Complications related to zygomatic implants placement: A retrospective evaluation with 5 years follow-up. Issue 7 (July 2021) - D'Agostino, Antonio; Lombardo, Giorgio; Favero, Vittorio; Signoriello, Annarita; Bressan, Anna; Lonardi, Fabio; Nocini, Riccardo; Trevisiol, Lorenzo
Abstract: This retrospective study assessed zygoma implants in patients treated for upper maxilla extreme atrophy, trauma, cleft palate, or failed reconstruction. The implants were placed using Quad (4 zygoma implants) or mixed (zygoma and conventional implants in premaxilla) surgical technique, with intra-sinus or extra-sinus approach, followed by immediate or deferred loading. Clinical and radiographic evaluations were carried out at 5-year follow-up from loading. Implant survival, symptoms and signs of sinusitis, radiological alterations in terms of mucosal thickening or obliteration of the maxillary sinuses, oroantral communications, and peri-implant soft tissues were examined. A total of 42 patients, with 116 zygoma implants, were included in the study. The cumulative survival rate was 97.41%. One zygomatic bone fracture was assessed. Eight patients reported sinusitis, and two showed oro-antral communications. A comparison between mean pre- and post-operative Lund–Mackay scores showed a statistically significant increase of sino-nasal disease in the post-operative scores (p = 0.0019). Mucositis and gingival recession was observed in 21 and 8 implants respectively. Average recession was 2.52 ± 2.35 mm. According to our results, placement of zygoma implants has proved to be a predictable procedure, with a lower rate of severe complications compared to other treatment options in extreme upper jaw atrophy.